(untitled) (Malaysian Journal of Learning and Instruction, 2016)
Purpose – This paper reports on a part of a larger research project concerning the conceptualisation of English language speaking-in-class anxiety, attitudes to speaking English in class and self-ratings of English-speaking ability, and perceived sources of this situation-specific anxiety. Methodology – The participants in this study were 282 Thai university students of English as a foreign language (EFL) studying English Conversation courses at a university in Thailand. Levels of anxiety (on average and by dimensions) were investigated through questionnaires adapted from the Foreign Language Classroom Anxiety Scale (FLCAS). Attitudes towards oral English, self-ratings of English-speaking ability and sources of speaking anxiety were collated through semi-structured interview forms. Findings – The quantitative analysis indicated the existence of speaking-in-class anxiety among Thai EFL students at a moderate level. Levels of anxiety by dimensions, namely test-anxiety (TA), fear of negative evaluation (FNE) and communication apprehension (CA), were found to be moderate as well. However, TA and FNE were significantly dominant performance anxieties. Qualitatively, students’ positive attitudes towards speaking English in the classroom were reflected, whereas a negative rating for their spoken English ability was reported. Finally, the limited repertoire of students’ vocabulary was found to be their major source of speaking anxiety. Significance – This research urges awareness of anxiety-provoking factors in the EFL classroom as learners’ ability to communicate satisfactorily is both the learners’ goal of learning and the instructor’s goal of teaching. The findings have pedagogic implications in terms of affective aspects of learning, for students when making an effort to overcome speaking-in-class anxiety and for instructors when attempting to create a low-anxiety classroom.